Publication Trends in Surgical Treatment of Distal Radius Giant Cell Tumors Over the Past Five Years - Mujaddid Idulhaq; Pamudji Utomo; Denny Adriansyah (Indonesian Journal of Cancer, 2022)
Background: Surgical interventions such as intralesional curettage until the complete excision and reconstruction require distal radius GCT treatment. However, to maintain the wrist function and reduce recurrent tendency, a more comprehensive understanding is needed to decide on the best therapeutic option as the standard strategy to achieve complete resection and functional outcomes. Therefore, this study aims to find the current treatment trends based on a literature study on distal radius GCT, emphasizing their potential outcomes. Methods: The search strategy using the PubMed search engine (https://pubmed.ncbi.nlm.nih. gov/) was conducted on September 21, 2020, with the keywords: “distal radius giant cell tumor”. The search resulted in 261 articles, and they were filtered by “published in the last five years,” which yielded 67 articles. These articles then underwent further screening, resulting in 40 articles for the analysis. Results: For article types, there were 27% (11/40) prospective studies, 32% (13/40) retrospective studies, 5% (2/40) systematic reviews, 27% (11/40) case reports, and 5% (2/40) case series. For the case series, more than ten cases were reported in both articles. There were 47 treatments in those total articles, and there were two types of GCT excision: intralesional curettage (extended and non-extended) (74.4%; 35/47) and en bloc (wide) resection (25.5%; 12/47). Conclusions: The total number of articles published in the last five years on the distal radius increased in 2020. Most types of articles were retrospective studies, followed by case reports and prospective studies. The most common treatment published in the last five years is intralesional curettage than en bloc resection, with excellent results in intralesional curettage’s functional outcome.